SUMBANGSIH PEMIKIRAN DALAM KONTEKS GKPS: MENUJU PELAYANAN KONSELING PASTORAL YANG HOLISTIK - Saragih, Jan Christian Wismar; Tarihoran, Joshua Tobias Velusiando Hezron (The Way: Jurnal Teologi dan Kependidikan, 2025)
This article explores how and what holistic pastoral counseling is and how it can be done in the context of the GKPS church. This is because, although the service already exists, it has not been implemented optimally. Therefore, the purpose of this article is to maximize and develop the potential of this service. This development takes into account the context of the GKPS church as a Protestant church with a strong cultural and ethnic inculturation background. Efforts to develop this potential are carried out by providing useful ideas for the church. Namely, applicable and useful suggestions that can be carried out by the church. This is important considering two things, namely the urgent need of the congregation for holistic pastoral counseling services and the positive impact and benefits that can be provided pastoral counseling. The contribution of ideas is obtained from a qualitative research method that combines literature study methods and interviews with informants. Thus, this research can produce an offer of new ideas that are useful both for further development and for implementation in GKPS.